Identificación y evaluación de los factores de riesgos ergonómicos en las áreas de lijado, administrativas y despacho de la empresa “La Fábrica del Mueble”, ubicada en el sector de La Avelina, para el mejoramiento de los sistemas de trabajo.” - Flores Taipe, Kevin Alexander (2021)
It should be noted that this work corresponds to the ergonomic risk study that, they affect the health and integrity of the workers who carry out their activities in the área of sanding, administrative and office of the company La Fábrica del Mueble with the purpose to protect the safety of employees, applying the methods of ergonomic evaluation REBA, OWAS and MAC, internationally endorsed, what allows to obtain the results of the risks under study in the mentioned areas. Through this ergonomic study, each of the efforts made can be reduced for each of the employees during their working day, increasing performance and motivation, giving us a positive effect for the improvement of the systems of job. The methodology used is based on field research, documentary, bibliography, in order to obtain data for the realization of the project, the elaboration of the same causes a benefit both for the workers and for the company, proposing alternatives to minimize ergonomic risks.